2012
DOI: 10.3109/02656736.2011.654374
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil to lymphocyte ratio might predict poor prognosis for colorectal liver metastasis after percutaneous radiofrequency ablation

Abstract: Elevated NLR (>5) might predict more extrahepatic metastasis and poorer survival for patients with CRLM after RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Halazun et al 15 have suggested 2 potential mechanisms through which a high NLR may be associated with poorer outcome: first, patients with an elevated NLR are relatively lymphocytopenic, resulting in a poorer lymphocyte-mediated immune response to malignancy and therefore an increased potential for tumor recurrence 16 ; second, a relatively high neutrophil count may aid in the development and progression of a neoplasm through release of vascular endothelial growth factor, a proangiogenic factor thought to be integral to tumor development. 18 This study provides some evidence to challenge the NLR threshold of 5 that has been recommended by several groups, [5][6][7][8][9][10] which was originally extrapolated from a Slovakian study of critically ill patients that showed an NLR of greater than 5 was associated with a poorer outcome. Longer follow-up may identify differences in OS between NLR groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Halazun et al 15 have suggested 2 potential mechanisms through which a high NLR may be associated with poorer outcome: first, patients with an elevated NLR are relatively lymphocytopenic, resulting in a poorer lymphocyte-mediated immune response to malignancy and therefore an increased potential for tumor recurrence 16 ; second, a relatively high neutrophil count may aid in the development and progression of a neoplasm through release of vascular endothelial growth factor, a proangiogenic factor thought to be integral to tumor development. 18 This study provides some evidence to challenge the NLR threshold of 5 that has been recommended by several groups, [5][6][7][8][9][10] which was originally extrapolated from a Slovakian study of critically ill patients that showed an NLR of greater than 5 was associated with a poorer outcome. Longer follow-up may identify differences in OS between NLR groups.…”
Section: Discussionmentioning
confidence: 91%
“…5 The second group includes patients with metastatic liver disease where a value greater than 5 has been associated with poorer overall survival (OS) in patients undergoing both liver resection with chemotherapy and chemotherapy alone. 7 Finally, the third area where the use of preoperative NLR has been proposed is as a predictor of recurrence in patients undergoing curative surgery for CRC with no known metastases, where values of above 3 or 5 have been associated with poorer OS and disease-free survival (DFS). 7 Finally, the third area where the use of preoperative NLR has been proposed is as a predictor of recurrence in patients undergoing curative surgery for CRC with no known metastases, where values of above 3 or 5 have been associated with poorer OS and disease-free survival (DFS).…”
mentioning
confidence: 99%
“…An elevated NLR was recognized as an independent poor prognostic factor for various malignancies [22], [25], [26], [28], [29]. In the “NLR”, “N” represents the number of circulating neutrophils, and it could represent the levels of circulating angiogenesis-regulating chemokines, growth factors and proteases which are major contributors to tumor related angiogenesis [30], [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported an association between high NLR and colorectal tumour size [41], poor differentiation [4] and mucinous type [42]. In contrast, only a couple of investigators failed to show any association between NLR and clinicopathological features or Dukes staging [43,44]. The pre-treatment value of NLR has also shown predictive value in guiding treatment regimens: for example, Kim et al [32] reported a poor rate of pathological complete response in patients with high pre-treatment NLR, undergoing preoperative chemoradiotherapy for locally advanced rectal cancers.…”
Section: Discussionmentioning
confidence: 99%